High-Fat Diet Increases Amylin Accumulation in the Hippocampus and Accelerates Brain Aging in hIAPP Transgenic Mice - Xi, Xiao-Xia; Sun, Jing; Chen, Hai-Chao; Chen, An-Di; Gao, Li-Ping; Yin, Jie; Jing, Yu-Hong (Frontiers in Aging Neuroscience, 2019)
The accumulation of human islet amyloid polypeptide （hIAPP） in pancreatic islets under induction by a high-fat diet plays a critical role in the development of type-2 diabetes mellitus (T2DM). T2DM is a risk factor of late-onset Alzheimer’s disease (AD). Nevertheless, whether hIAPP in combination with hyperlipidemia may lead to AD-like pathological changes in the brain remains unclear. hIAPP transgenic mice were fed with a high-fat diet for 6 or 12 months to establish the T2DM model. The accumulation of amylin, the numbers of Fluoro-Jade C (FJC)-positive and β-gal positive cells, and the deposition level of Aβ42 in the hippocampi of the transgenic mice were detected by using brain sections. Cytoplasmic and membrane proteins were extracted from the hippocampi of the transgenic mice, and the ratio of membrane GLUT4 expression to cytoplasmic GLUT4 expression was measured through Western blot analysis. Changes in the cognitive functions of hIAPP transgenic mice after 12 months of feeding with a high-fat diet were evaluated. hIAPP transgenic mice fed with a high-fat diet for 6 or 12 months showed elevated blood glucose levels and insulin resistance; increased amylin accumulation, number of FJC-positive and β-gal positive cells, and Aβ42 deposition in the hippocampi; and reduced membrane GLUT4 expression levels. hIAPP transgenic mice fed with a high-fat diet for 12 months showed reductions in social cognitive ability and passive learning ability. A high-fat diet increased amylin accumulation in the hippocampi of hIAPP transgenic mice, which presented AD-like pathology and behavior characterized by neural degeneration, brain aging, Aβ42 deposition, and impaired glucose utilization and cognition.